2019
DOI: 10.1126/sciadv.aav7127
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast chemical imaging by widefield photothermal sensing of infrared absorption

Abstract: Infrared (IR) imaging has become a viable tool for visualizing various chemical bonds in a specimen. The performance, however, is limited in terms of spatial resolution and imaging speed. Here, instead of measuring the loss of the IR beam, we use a pulsed visible light for high-throughput, widefield sensing of the transient photothermal effect induced by absorption of single mid-IR pulses. To extract these transient signals, we built a virtual lock-in camera synchronized to the visible probe and IR light pulse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
169
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 116 publications
(177 citation statements)
references
References 46 publications
0
169
0
Order By: Relevance
“…In this work, we additionally harness the capability of QPI to computationally synthesize the 3D spatial-frequency aperture of the imaging system 2,22 . This enables us to further achieve (3) the higher lateral spatial resolution by the expanded bandwidth of the synthetic aperture that surpasses the numerical aperture (NA) of a single objective lens which poses the diffraction limit in other farfield MVI techniques [6][7][8][9][10][11][12][13][14][15][16][17][18]20 and (4) decoupling the undesired MIR absorption effect of the surrounding aqueous medium, which is the well-known problem of MIR microscopy in general, by the depth-resolving power offered by the axial bandwidth of the 3D synthetic aperture.…”
Section: Mv-qpi the Concept Of Mv-qpi Is Illustrated Inmentioning
confidence: 99%
“…In this work, we additionally harness the capability of QPI to computationally synthesize the 3D spatial-frequency aperture of the imaging system 2,22 . This enables us to further achieve (3) the higher lateral spatial resolution by the expanded bandwidth of the synthetic aperture that surpasses the numerical aperture (NA) of a single objective lens which poses the diffraction limit in other farfield MVI techniques [6][7][8][9][10][11][12][13][14][15][16][17][18]20 and (4) decoupling the undesired MIR absorption effect of the surrounding aqueous medium, which is the well-known problem of MIR microscopy in general, by the depth-resolving power offered by the axial bandwidth of the 3D synthetic aperture.…”
Section: Mv-qpi the Concept Of Mv-qpi Is Illustrated Inmentioning
confidence: 99%
“…At microscale, the 3ω method has been used to measure the thermal conductivity of materials and single cells 17 , 18 . A number of microscopes have been developed that take advantage of the local change in refractive index upon chromophore absorption, some of which use vibrational spectroscopy to extract molecular content 15 , 19 , 20 . Macroscopically, widefield thermal imaging is routinely used in industrial applications such as assessment of electrical connections and bulk material characterization, while DTI has been increasingly used in medical applications 21 , 22 .…”
Section: Discussionmentioning
confidence: 99%
“…While progress in classical IR microscopy is hindered by fundamental physical limitations (e.g., diffraction limit), our results reveal the potential of IR-OH for superresolution IR imaging, largely improved coverage, and suppression of IR scattering that can be employed for unforeseen, transformative applications in histopathologic imaging. Further, the interferometric detection in IR-OH provides a sensitivity advantage over previous photothermal techniques that relied on beam deflection from IR absorption-induced refractive index change (41,42,44,45,48,53). While our method measures the physical response of expansion directly, deflection methods measure the refractive index change that occurs upon deflection and need higher probe intensity than we have employed.…”
Section: Significancementioning
confidence: 99%
“…The need for sample scanning renders them impractical for the rapid acquisition of spectrally resolved photothermal datasets in cases of large samples such as tissue sections for pathology. Recent studies have demonstrated wide-field measures of photothermal absorption and scattering (52,53). Despite providing optical compatibility, however, these methods provide fields of view and pixel counts that are much smaller than direct absorption IR microscopy (54).…”
Section: Significancementioning
confidence: 99%